Improving The Skill of Early Childhood Education Teachers in Making Lesson Plans Through an Andragogy-Based Training - Novitasari, Dewi; Sugito, Sugito (Universitas Negeri Semarang, 2018)
This study aimed to improve: (1) the learning process of early childhood education (ECE) teachersÂ in making lesson plans, (2) the ability of ECE teachers in making lesson plans. This study is action research that adopted the model developed by Kemmis and Mc. Taggart consisting of planning, implementation of the action, observation, and reflection. The data collection was done through observation, interviews, and document analysis. The data analysis used was the qualitative analysis and descriptive descriptive analysis. The result of the study showed that there was improvement in:Â (1) the training participants; learning activities (studentsâ€™ cooperation, discipline, participation, commitment, bravery in expressing opinions, ability to execute learning process, and learning independence), (2) the ability of ECE teachers in making lesson plans